Static Analysis of Steel Fiber Concrete Beam With Heterosis Finite Elements - Haido, James H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2014)
Steel fiber is considered as the most commonly used constructional fibers in concrete structures. The formulation of new nonlinearities to predict the static performance of steel fiber concrete composite structures is considered essential. Present study is devoted to investigate the efficiency of utilizing heterosis finite elements analysis in static analysis of steel fibrous beams. New and simple material nonlinearities are proposed and used in the formulation of these elements. A computer program coded in FORTRAN was developed to perform current finite element static analysis with considering four cases of elements stiffness matrix determination. The results are compared with the experimental data available in literature in terms of central deflections, strains, and failure form, good agreement was found. Suitable outcomes have been observed in present static analysis with using of tangential stiffness matrix and stiffness matrix in second iteration of the load increment.